Library Anxiety Di Upt Perpustakaan Uin Datokarama Palu: Analisis Faktor Penyebab - Aziza, Wafiq; Arifin, Nur; Jusmiati, Jusmiati (Literatify: Trends in Library Developments, 2025)
This study aims to analyze the factors contributing to library anxiety among students at UIN Datokarama Palu. Employing a mixed-methods approach with a sequential explanatory design, data were collected through a survey of 92 students and in-depth interviews with 7 informants. The quantitative findings indicate that the overall level of library anxiety among students falls into the moderate category, with library comfort barriers obtaining the highest score (mean 3.6; 64.8%). The contributing factors are classified into internal factors, such as lack of self-confidence, fear of asking questions, and limited information literacy, as well as external factors, including unwelcoming librarian services, inadequate physical facilities, and noisy library environments. The qualitative findings reinforce these results by highlighting the significance of psychological aspects and the quality of librarian–student interactions in shaping students’ library experiences. The implications of this study suggest that library anxiety should not be perceived merely as an individual barrier, but also as an institutional challenge that influences the quality of library services. Therefore, libraries should take strategic steps, such as improving physical comfort, providing information literacy and library orientation programs, offering practical training in technology use, and strengthening librarians’ competencies in empathy-based services. These efforts are expected to foster a more inclusive, comfortable environment that supports students’ academic success.